The Importance of Parents' Role in Shaping Early Childhood Independence - Raisha Chana Nurhaliza; Hayani Wulandari (al-Afkar, Journal For Islamic Studies, 2024)
Parents serve as guides, teachers, motivators, and role models for their children. They can foster independence in their children by providing a supportive environment and opportunities for independent activities. Parents can also guide their children by offering appropriate guidance and instructions. Motivating children through praise and support is another role that parents play. The objective of this research is to understand the role of parents in shaping the independence of early childhood. Independence is a crucial aspect of the development of young children. The research employs a descriptive method with a qualitative approach, drawing data from parents of early childhood education students. The research instruments include two techniques: interviews and questionnaires. The study utilizes a descriptive method with a qualitative approach. The results of the research are derived from the questionnaire on the Role of Parents in Developing Independence in Early Childhood, which is categorized as follows: 1.)The category where parents excel constitutes 50% with a total of 6 respondents. 2.)The category of parents being proficient comprises 25% with a total of 3 respondents. 3.)The category of parents having a limited proficiency constitutes 16.67% with a total of 2 respondents. 4.)The category where parents do not have proficiency comprises 8.33% with a total of 1 respondent.